Spatiotemporal Differentiation of Fertilizer and Pesticide Use and Its Driving Factors in the Yangtze River Delta of China: An Analysis at the County Scale - Ke Wu; Cheng Chen (Land)
Reducing fertilizer and pesticide use is a crucial path for the green transformation of agricultural production, which has garnered sustained attention in research on sustainable agricultural development. Based on the theoretical analysis, this article analyzes the spatiotemporal evolution characteristics of fertilizer and pesticide usage intensity (FUI and PUI) in the Yangtze River Delta (YRD) over the past 20 years and uses a Two-Way Fixed Effects Model to test their impacts and mechanisms. Findings show that agricultural development in the YRD shows a pattern of specialization and intensification with a significant north–south divide, with zero growth and reduction in fertilizer and pesticide use across the region from 2010 to 2015, but the current FUI and PUI are still nearly three and five times higher than the global average. Over the past 20 years, the FUI is high in the north and low in the south, high in the plains and low in mountainous-hilly areas, and high in suburban areas and low in remote counties. Adversely, the PUI is high in the south and low in the north, high in mountainous-hilly areas and low in plains, and high in suburban areas and low in remote counties. The FUI and PUI of characteristic agricultural areas of fruit, tea, and forestry in southern Anhui and southwestern Zhejiang, as well as the agroecological and facility agriculture clusters in southern Jiangsu and the suburbs of Shanghai, have approached the peak and successfully moved into the new green development stage earlier compared to other areas. In contrast, the grain and oil production plains areas along the Yangtze River, the coast, in northern Anhui, and in northern Jiangsu are relatively lagging behind. The combination of soil, water, light, and heat resource conditions and modes of agriculture production shape the absolute figures of FUI and PUI, and factors such as the level of local economic development and public fiscal expenditure significantly influence the trajectories of spatiotemporal differentiation in the progress of reducing fertilizer and pesticide in the YRD.